The Product Features, Functions, and Benefits of Seafood Products for Competitive Repositioning - Nurliza, Nurliza; Suharyani, Anita; Nugraha, Aditya (Universitas Muhammadiyah Yogyakarta, 2021)
The global demand for seafood products increased in a dynamic environment. Still, fails to achieve competitive positioning due to labeling, unattractive and unprofitable targeted segments, and less preferred quality and features. Thus, this study tried to create competitive positioning through features, functions, and benefits of seafood product attributes. The results arranged through consumer characteristics, consumer preference with conjoint analysis, market identification and competition with regression analysis, Multidimensional Scaling, and Correspondence Analysis from 206 respondents. The results prove that (i) canned fish, dried fish, and salted fish competed on freshness, durability, and food safety (labels); (ii) shredded fish, surimi, and pedak competed on density, taste, physiological function, and easy-to-use feature; (iii) crackers competed on taste, social function, and psychological function; (iv) shrimp paste competed on shape, color, surface condition, texture, additive content, and chemicals. The implications of the results: (i) transported and packed to processing plants and food storage facilities; (ii) an increase in food diversity, food fortification, and supplementation; (iii) cultural congruence between the product and the market with certain packaging designs, launch timing, and advertising; (iv) several methods of process, such as quick freezing and cook-chilling, pasteurized before packed or retort pouch and natural food additives.